Psychometric Properties of Turkish Version of the Dutch Objective Burden Inventory - Canan Demir Barutcu, PhD; Hatice Mert, PhD; Murat Bektaş, PhD (Elsevier, 2015)
Purpose: The purpose of this study was to assess the psychometric properties of the Dutch Objective Burden Inventory (DOBI) for the Turkish society. Methods: This is a descriptive, methodological study. The sample was composed of 230 heart failure patients' caregivers. Results: The DOBI was translated using translation and back-translation. The translated Turkish version was submitted to eight experts who analyzed it for its content validity. Scores from the experts were evaluated using the Kendall W analysis, and no statistically significant difference was found among the scores (Kendall W = .13, p = .338). In the confirmatory factor analysis, factor loading was found to be between 0.75 and 1.00 for all subscales. Thus, the DOBI demonstrated acceptable internal consistency (the components displayed α scores from .96 to .99), good test-retest reliability (no statistically significant differences were found, p > .050). Conclusions: The Turkish version of the DOBI scale is a valid and reliable tool for the Turkish population. It can be used in nursing practices and research.